Synthesis of a New Polymeric Host Material for Efficient Organic Electro-Phosphorescent Devices - Hwang, Do-Hoon; Park, Moo-Jin; Eom, Jae-Hoon; Shim, Hong Ku; Lee, Seongtaek; Yang, Nam Choul; Lian, Duan; Suh, Min Chul; Chin, Byung Doo (AMER SCIENTIFIC PUBLISHERS, 2008)
We have synthesized a new polymeric host material for phosphorescent dyes, which can be used in phosphorescent light-emitting layers. An alternating copolymer, composed of N-alkyl-carbazole and tetramethylbenzene units was synthesized through the Suzuki coupling reaction. We fabricated electro-phosphorescent devices using the synthesized polymeric host doped with solution-processible green and red phosphorescent dyes. Light-emitting devices have an ITO/PEDOT/polymer+dopant/Balq(3)/Alq(3)/LiF/Al configuration. The device containing one of two studied green dopants (designated as green 1) in the polymeric host showed the best performance, with a maximum luminous efficiency of 29 cd/A. A thin film of this polymeric was successfully patterned by laser-induced thermal imaging (LITI), and an electro-phosphorescent device was fabricated using the patterned film. This patterned device showed performance characteristics similar to those of a spin-coated device.